Publishing, bookselling and the World Wide Web - Amanda Spink (Information Research: An International Electronic Journal)
This working paper brings together concepts and ideas about the role of information in the future of humanity. Different views have emerged within the international debate on sustainable development - a global industrialization view centers on sustaining global industrialization and a new moral order that advocates societal downscaling and de-industrialization based on regional self-sufficiency to preserve humanity. This working paper briefly outlines these approaches to sustainable development and their relationship to information science research. Both views are distinguished by their approach to de-industrialization. Global industrialization includes pockets of de-industrialization of communities and regions, and societal down scaling includes a de-industrialization process to a sustainable community. De-industrialization is therefore a growing interdisciplinary area of research within sociology, urban planning and policy, and economics. However, information science research is becoming primarily concerned with the informational dimensions of the global industrialization - not de-industrialization. Despite the growing interdisciplinary literature on sustainable development and de-industrialization, the informational aspects of these important issues have yet to be fully explored.